The Potential for Cultivating Nutmeg (Myristica fragrans Houtt) in Rimbo Pengadang and Topos Districts of Lebong Regency - Nabella, Reni; Hindarto, Kanang Setyo; Barchia, Muhammad Faiz; Widiyono, Heru; Supanjani (TERRA : Journal of Land Restoration, 2024)
The research, conducted from January to September 2023, aimed to map land suitability classes for nutmeg plant development. The evaluation results are presented descriptively and involve three main stages: pre-survey, field survey, and tabulation with data analysis. Primary data collected for this research include soil analysis results from the laboratory, complemented by secondary data. The determination of land suitability utilizes matching techniques for each land characteristic. The actual land suitability results for nutmeg in Rimbo Pengadang and Topos Districts are categorized as follows: S3eh (37.77%) 14,460.93 ha, with the limiting factor being erosion hazard. S3na eh (37.07%), 14,175.10 ha, with limiting factors related to nutrient availability and erosion hazards, S3na (6.77%): 2,592.64 ha, with limiting factors in nutrient availability, S2wa nr na eh (5.34%): 2,044.04 ha, facing limitations in water availability, nutrient retention, nutrient availability, and erosion hazard, S3rc eh (1.30%) 499.43 ha, with a limiting factor for rooting media and erosion hazard, S3rc (0.90%): 346.35 ha, with a limiting factor in rooting media and N (not suitable) (9.10%) 3,484.74 ha. Regarding potential land suitability, the classes are as follows: S1 (44.89%) 17,186.07 ha, S2 (43.80%) 16,767.80 ha, S3rc (2.21%) 845.79 ha, and S3 (9.10%): 3,484.74 ha. The areas with potential for developing nutmeg plants in Rimbo Pengadang and Topos Districts, Lebong Regency, include secondary forest, mixed dry land farming, open land, and bushes.